Customer relationship management : concepts, applications and technologies - Prior, Daniel D., Buttle, Francis; Buttle, Francis; Maklan, Stan (Oxon, Routledge, 2024)
"This highly regarded textbook provides the definitive account of Customer Relationship Management (CRM) concepts, applications and technologies, focusing on how companies can create and maintain mutually beneficial relationships with customers. Readers will gain a thorough understanding of the conceptual foundations of CRM, see CRM in practice through illustrative case examples and exercises, and understand how to organise customer data gathering, analysis and presentation for decision-making. The book achieves these outcomes by first considering strategic CRM before moving into operational CRM and, finally, onto analytical aspects of CRM. The fifth edition has been fully updated to include: A series of new case examples to illustrate CRM within various regional and industrial contexts, including those relevant to large, medium, and small enterprises. A series of new exercises and discussion questions to help readers understand CRM concepts and to support pedagogical processes, particularly in higher education environments. A greater emphasis on managerial applications of CRM through new content to help guide managers. An updated account of new and emerging technologies relevant to CRM. Expanded coverage of customer experience (CX), customer engagement (CE) and customer journey management (CJM). Customer Relationship Management is essential reading for advanced undergraduate and postgraduate students studying CRM, Sales Management, Customer Experience Management and Relationship Marketing, as well as executives who oversee CRM functions. Online resources include an Instructor's Manual, chapter-by-chapter PowerPoint slides and a bank of exam questions"--
Includes bibliographical references and index.
Keywords: Customer relations -- Management